Diffusion tensor imaging in multiple sclerosis at different final outcomes. (25th July 2017) - Andersen, O.; Hildeman, A.; Longfils, M.; Tedeholm, H.; Skoog, B.; Tian, W.; Zhong, J.; Ekholm, S.; Novakova, L.; Runmarker, B.; Nerman, O.; Maier, S. E.
Abstract : Objectives: Methods to evaluate the relative contributions of demyelination vs axonal degeneration over the long‐term course of MS are urgently needed. We used magnetic resonance diffusion tensor imaging (DTI) to estimate degrees of demyelination and axonal degeneration in the corpus callosum (CC) in cases of MS with different final outcomes. Materials and methods: We determined DTI measures mean diffusivity (MD), fractional anisotropy (FA), and axial (AD) and radial (RD) diffusivities in the CC of 31 MS patients, of whom 13 presented a secondary progressive course, 11 a non‐progressive course, and seven a monophasic course. The study participants were survivors from an incidence cohort of 254 attack‐onset MS patients with 50 years of longitudinal follow‐up. As reference, we included five healthy individuals without significant morbidity. Results: In patients with secondary progression, compared to all other groups, the corpus callosum showed increased RD and reduced FA, but no change in AD. None of the parameters exhibited differences among non‐progressive and monophasic course groups and controls. Conclusion: Increased RD was observed in secondary progressive MS, indicating significant myelin loss. Normal RD values observed in the clinically isolated syndrome and non‐progressive groups confirm their benign nature. AD was not a characterizing parameter for long‐term outcome. Demyelination revealed by increased RD is a distinguishing trait for secondary progression.